Effect of hyaluronic acid in bone formation and its applications in dentistry. Issue 6 (9th April 2016) - Zhao, Ningbo; Wang, Xin; Qin, Lei; Zhai, Min; Yuan, Jing; Chen, Ji; Li, Dehua
Abstract: Hyaluronic acid (HA), the simplest glycosaminoglycan, participates in several important biological procedures, including mediation of cellular signaling, regulation of cell adhesion and proliferation, and manipulation of cell differentiation. The effect of HA on cell proliferation and differentiation depends on its molecular weight (MW) and concentration. Moreover, the properties of high viscosity, elasticity, highly negative charge, biocompatibility, biodegradability, and nonimmunogenicity make HA attractive in tissue engineering and disease treatment. This review comprises an overview of the effect of HA on cell proliferation and differentiation in vitro, the role of HA in bone regeneration in vivo, and the clinical applications of HA in dentistry, focusing on the mechanism underlining the effect of MW and concentration of HA on cell proliferation and osteogenic differentiation. It is expected that practical progress of HA both in laboratory‐based experiments and clinical applications will be achieved in the next few years. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1560–1569, 2016.